Interpretation and Review of the Basic Law of the Hong Kong Special Administrative Region - Chu, Liu Yiu (Columbia Journal of Asian Law, 1988)
Despite the democratic aspirations of the reformist minority in Hong Kong, the drafting of the Basic Law of the Hong Kong Special Administrative Region (SAR) of the People’s Republic of China (PRC) is dominated by the political realities that first brought British Prime Minister Margaret Thatcher to the conference table in Beijing in 1982. Two years later, these negotiations produced a draft of what is now the Joint Declaration of the Government of the United King- dom of Great Britain and Northern Ireland and the Government of the People’s Republic of China on the Question of Hong Kong (Joint Declaration).1 It was initialed by representatives of the U.K. and PRC governments in 1984 and was subsequently ratified and came into force on May 27, 1985. The document consists of a Joint Decla- ration, three Annexes and an associated Exchange of Memoranda, all of which should be considered together as a guide to the drafting and interpretation of the Basic Law itself.